Peran Reputasi Auditor Memoderasi Pengaruh Keputusan Investasi, Kebijakan Dividen dan Profitabilitas terhadap Nilai Perusahaan - Grace, Cecilia; Suhartono, Sugi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2025)
Firm value is an important aspect to describe the success of the company's owners and shareholders, which is often associated with the stock price, which is often used as a tool to influence investors' views on a company. Therefore, this study aims to determine the effect of investment decisions, dividend policy, and profitability on firm value moderated by auditor reputation. The object of this research is 21 Consumer non-Cyclicals companies listed on the Indonesia Stock Exchange for the period 2019 - 2022 so that 84 sample data are obtained. The sampling technique in this study used non-probability sampling technique with purposive sampling method. This study uses an analysis method consisting of descriptive statistical analysis, data pooling test, classical assumption test, moderated regression analysis (MRA), coefficient of determination test, F statistical test, and t statistical test. The conclusion of this study is that there is sufficient evidence that profitability and investment decisions have a positive influence on firm value. While there is not enough evidence that dividend policy has a positive effect on firm value. Then there is not enough evidence that auditor reputation is able to moderate the positive influence of investment decisions, dividend policy and profitability on firm value.